Program Pendampingan dan Edukasi tentang Pubertas pada Siswa SMP Muhammadiyah 1 Kota Pontianak - Lidia Hastuti; Ridha Mardiani; Erwan Syahrudin; Hanafi Hanafi; Vivit Wiyandani; Eva Mayandari; Meta Trisyya; Uswatul Hasanah (Jurnal Abdimas Kesehatan (JAK), 2022)
Sources of information about adolescent reproductive health must be provided correctly and appropriately according to their growth and development, both informally and formally. The problem that often occurs in students is the emergence of anxiety when they first experience menstruation. Students seem unprepared and embarrassed to tell their parents/teachers about the problems they are facing. Assistance for adolescents in dealing with puberty needs to be done to increase adolescent knowledge and be psychologically ready to face puberty. Outcome: The target of care for society is to increase students' knowledge about puberty and reproductive organ care at prepubertal age. The output target is the publication of mass media or the publication of the Abdimas Health journal. Methods: Assistance and education program for adolescents about puberty and reproductive organ care in junior high school. Results: Program implementation proved effective in increasing adolescent knowledge about puberty and sexual organ care.